“Fata Morgana”: ancora su strabismi e asincronie - Berardino Palumbo (Archivio Antropologico Mediterraneo)
This paper deals with some of the theoretical issues raised, during the last years, by some Fabio Dei's contributions and the debates they have produced. In particular, I argue that the "critical anthropology" identified in those interventions as a polemical objective, rather than an "invention" can be read as a projection, in the national academic field, of theoretical tensions that had crossed the Anglophone North American anthropologies in the late '90s of the last century. Having very quickly presented those international scenarios, I point out how in them (and partly in the national scene itself) many of the theoretical issues that emerged in those years then led to a radical reconfiguration of current and basic notions, research practices and styles of ethnographic representation; and therefore it is proposed that the discussion, even polemical, should be able to be declined on the level of concrete outcomes of research. Finally, I speculate, just as quickly, on the asynchronisms and arrhythmias between trends operating in the North American and domestic academic-scientific fields, and their possible political implications